2021
DOI: 10.25115/eea.v39i4.4493
|View full text |Cite
|
Sign up to set email alerts
|

The Online Shoppers’ Behavioral Intentions, E-Satisfaction, the Pathway to Repurchase Behavior: A Quantitative Analysis

Abstract: Online shopping is catching new heights, the repetition of consumer buying behavior is still a challenge for businesses. The current study investigates the antecedents of consumer repurchase intentions that bridge consumer repurchase behavior through e-satisfaction by extending the technology acceptance model. A questionnaire was developed with additional constructs of consumer behavior after an extensive review of the literature. A total of 607 usable responses were received from Pakistani university students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…Therefore, studies have tied behavioral intentions with people's choice to buy or people's will to give recommendations (i.e., sharing experiences through word-of-mouth communication) and their choices to revisit the same place [59]. Furthermore, Chen & Tsai [60] also mentioned behavioral intentions as an assessment carried out by the visitors for consuming a product in the future [61]. Behavioral intentions are demonstrated boding the possibility of revisiting the same store or the willingness of visitors to recommend the store to others.…”
Section: Behavioral Intentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, studies have tied behavioral intentions with people's choice to buy or people's will to give recommendations (i.e., sharing experiences through word-of-mouth communication) and their choices to revisit the same place [59]. Furthermore, Chen & Tsai [60] also mentioned behavioral intentions as an assessment carried out by the visitors for consuming a product in the future [61]. Behavioral intentions are demonstrated boding the possibility of revisiting the same store or the willingness of visitors to recommend the store to others.…”
Section: Behavioral Intentionmentioning
confidence: 99%
“…In previous studies, it was suggested that the value perceived by customers and behavioral intention affect the repurchase pattern [94]. Thus, behavioral intention is an antecedent of actual loyalty [41] and significantly contributes to the repurchase pattern [61]. Loyalty shows that customers commit to repurchasing [95].…”
Section: Relationship Between Behavioral Intentions and Repurchasementioning
confidence: 99%